2019
DOI: 10.3390/molecules24173164
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of CB2 Receptors in the Neurobehavioral Effects of Catha Edulis (Vahl) Endl. (Khat) in Mice

Abstract: There is behavioral evidence for the interaction between crude khat extract and the endocannabinoid system, whereby the endocannabinoid system alters khat extract-mediated behavioral effects through modulation of the monoaminergic system. The objective of this study was to investigate the role of the endocannabinoid system on the neurobehavioral effect of khat extract in mice following concomitant administration of khat extract and the CB2R agonist, JWH133. Locomotor activity test, immunohistochemistry, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 73 publications
(94 reference statements)
0
9
0
Order By: Relevance
“…Recent findings suggested that B2R modulates the behavioral effects in the CNS [ 9 ], including mood and emotional behavior. Evidence suggests CB2R plays a role in food intake, body weight control and eating disorders [ 133 , 134 , 135 ], depression and anxiety [ 101 , 105 , 134 ], drug addiction [ 136 ], psychosis and schizophrenia-like behavior [ 137 , 138 , 139 ] and synaptic plasticity underlying cognitive functions [ 135 , 138 ].…”
Section: Role Of Cb2r In Various Cns Disordersmentioning
confidence: 99%
“…Recent findings suggested that B2R modulates the behavioral effects in the CNS [ 9 ], including mood and emotional behavior. Evidence suggests CB2R plays a role in food intake, body weight control and eating disorders [ 133 , 134 , 135 ], depression and anxiety [ 101 , 105 , 134 ], drug addiction [ 136 ], psychosis and schizophrenia-like behavior [ 137 , 138 , 139 ] and synaptic plasticity underlying cognitive functions [ 135 , 138 ].…”
Section: Role Of Cb2r In Various Cns Disordersmentioning
confidence: 99%
“…The possible explanation for this finding could be the effect of khat through its constituents upon activation of α2 and 5HT7 receptors and inhibition of ACh thereby modulating airway smooth muscle contraction (Freud-Michel et al, 2008). The results by Geresu et al (2019) suggested the CB2Rs selectively interact with khat extract-mediated locomotor effects and could be utilized as therapeutic target in central nervous system movement disorders associated with dopamine dysregulation.…”
Section: Alteration the Metabolizing Enzymes Activity By Khatmentioning
confidence: 99%
“…CB2Rs are mainly expressed post-synaptically and their activation inhibits postsynaptic neuronal function through membrane potential hyperpolarization ( 53 ), and also reported presynaptically in some terminals. Thus, CB2Rs are involved in modulating a variety of behavioral effects in the CNS with reports that CB2Rs modulate food intake, body weight ( 54 , 55 ), depression and anxiety ( 14 , 56 ), drug addiction ( 57 , 58 ) and schizophrenia-like behavior ( 59 ). Brain CB2Rs are expressed at low levels under physiological conditions; however, in pathological conditions, such as neuropathic pain ( 60 ), stroke ( 61 ), traumatic brain injury (TBI) ( 62 ), neurodegenerative diseases ( 57 , 63 , 64 ) or drug addiction ( 65 , 66 ), their expression is enhanced and up-regulated.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CB2Rs are involved in modulating a variety of behavioral effects in the CNS with reports that CB2Rs modulate food intake, body weight ( 54 , 55 ), depression and anxiety ( 14 , 56 ), drug addiction ( 57 , 58 ) and schizophrenia-like behavior ( 59 ). Brain CB2Rs are expressed at low levels under physiological conditions; however, in pathological conditions, such as neuropathic pain ( 60 ), stroke ( 61 ), traumatic brain injury (TBI) ( 62 ), neurodegenerative diseases ( 57 , 63 , 64 ) or drug addiction ( 65 , 66 ), their expression is enhanced and up-regulated. The inducible nature of CB2Rs during events with underlying inflammation can make them a potential therapeutic target and ligands that activate or inhibit the activity of CB2Rs might be used to treat different disorders without causing profound adverse drug and intoxicating effects ( 67 ).…”
Section: Introductionmentioning
confidence: 99%